Calcium and lactate in the fetal-to-neonatal transition. (12th December 2022) - Zanardo, Vincenzo; Straface, Gianluca; Sandri, Andrea; Severino, Lorenzo; Crivellaro, Carlo; Garani, Gianpaolo; Simbi, Alphonse
Abstract: Objective: To explore the relationship between calcium and lactate in arterial cord blood of healthy term neonates in response to the stress of labor. Methods: This was a prospective cohort study of consecutive, vaginal, term births in a community medical center (April 2029 to February 2020). Calcium and lactate were measured in cord blood gas analysis immediately after delivery. Results: In the arterial cord blood of 480 neonates, calcium levels were 1.5 (1.4; 1.5) mmol/L and lactate levels were 3.8 (2.9; 4.9) mmol/L. Calcium and lactate showed a statistically significant positive correlation (Pearson's correlation, r  = 0.15, p  = .001). Calcium levels had a significant positive correlation with PaCO2 and a significant negative correlation with pH, PaO2, HCO3 −, and ABE levels. Multivariable analysis models confirmed that calcium levels were associated with HCO3 −, gestational age, and birth weight, all accounting for 7% of the variability. Conclusion: In healthy term vaginally delivered neonates, it was found that calcium and lactate were strongly correlated, together pointing to a neonatal response to the stress of labor and delivery. Cord blood calcium regulation may have an ancillary role in defining neonatal adaptation to extrauterine life.